A Ruthenium Based Organometallic Complex for Biosensing that is both a Stable Redox Label and a Homobifunctional Linker. Issue 5 (15th January 2015) - Lee, Yeng Ying; Parker, Stephen G.; Barfidokht, Abbas; Alam, Muhammad Tanzirul; Walker, D. Barney; Messerle, Barbara A.; Gooding, J. Justin
Abstract A stable ruthenium‐based redox label, Ru(acetylacetonate)2(bipyridine‐NH2), has been synthesized with the target of circumventing the problem associated with the use of ferrocene for biosensing in solutions containing chloride ions. The redox species was shown to be highly stable with repeated cycling in biological buffers as well as being amenable to surface coupling reactions. To demonstrate the latter, the redox label was anchored onto a self‐assembled monolayer of 6‐mercaptohexanoic acid, using carbodiimide coupling, followed by binding of a pentapeptide to the redox label.